The Use of Sundanese Slang by Teenagers in an Internet-Based Chat Application - Gifta Annisa Auni (Passage, 2018)
The research aims to investigate the types of Sundanese slang used by teenagers on a social media LINE and the social factors influencing the use of slang. This research applies a descriptive qualitative research method. The participants of this research were 28 students of a senior high school in Bandung, whose ages are in the middle of 16-18. The data were collected through conversations on social media LINE. To analyze the data, the theory proposed by Allan and Burridge (2006) and other theory of slang types were implemented to identify the types of Sundanese slang. To examine possible factors which influence the use of Sundanese slang by the teenagers, this study uses Holmes (2003) social factors and social dimensions of language use. The findings reveal that the participants express slang on social media LINE. Those slang words are categorized into five types. However, the Sundanese slang found in this research only matched with the two types: imitative type and clipping type. In addition there are two other types of slang found in the research outside the categories proposed by Allan and Burridge (2006), namely loan or borrowing and back slang. The most widely used type of slang is clipping type with 57 %, followed by imitative type with 20%, loan/borrowing type with 20%, and back slang with 3%. The teenagers tend to use the clipping type because they want to write as fast as possible, in order to save a bit of their time. Furthermore, the findings show that there are three social factors influencing the use of slang by the teenagers, namely participants, settings, and topics. This study confirms Zhou (2013), Pedersen (2009), Reyes (2005), and Tannen (1996) who state that male tends to use more slang rather than the female. The present research is also in line with Richter (2006) and Reyes (2005) who claim that the use of slang is influenced by the topics. However, this study contradicts Warsa (2013) who asserts that Sundanese slang is not influenced by other languages and there is almost no clipping on it. Whereas, the results of the present research show that the Sundanese slang used by the youth is influenced by Indonesian and English, and the most frequent slang used by the youth is the clipping type. Keywords: Slang, Sundanese slang, social media, slang types, and social factors